Biomechanical characteristics of taekwondo athletes: kicks and punches vs. laboratory tests - Busko, K.; Nikolaidis, P. T. (Biomedical Human Kinetics, 2018)
Study aim: The aim of the study was to examine biomechanical characteristics of taekwondo athletes comparing kicks and punches with laboratory tests of muscle strength and power. Material and methods: Six male taekwondo athletes participated in this study. Measurements of maximal punching with the rear hand (hook and straight punches) and kicking (Apdolio and Dwit Chagi) force were performed on a boxing dynamometer. Also, the following laboratory tests were performed: jump height and power output in counter movement jump (CMJ) and spike jump (SPJ), muscle strength for 10 muscle groups and force-velocity (F-v) relationship. Results: Mean maximal straight and hook punching forces were 1659.2 ± 254.2 N and 1843.8 ± 453.3 N, respectively. Maximal Apdolio rear leg, Apdolio lead leg and Dwit Chagi rear leg kicking forces were 3541.3 ± 1130.3 N, 3205.3 ± 965.1 N and 3568.0 ± 1306.0 N, respectively. The heights of jumps were 0.501 ± 0.040 m (CMJ) and 0.554 ± 0.034 m (SPJ). A strong correlation between the maximal force of a punch and maximal joint torques was observed. Conclusions: The values of kicking forces developed in a simulated fight were lower than the forces developed in the test of individual kicks. Strong relationships were observed between leg power developed in the SPJ and force of individual Apdolio kicks performed with the lead (r = 0.87, p < 0.05) and rear leg (r = 0.74). Based on these findings, it was concluded that maximal joint torques and height of the SPJ could be used as a proxy of kicking force.